CHONDROPROTECTIVE DRUG ALFLUTOP IN THE TREATMENT OF OSTEOARTHRITIS - G V Lukina; Y A Sigidin (Научно-практическая ревматология)
Summary Aljlutup is an effective and well tolerable drug which not only decreases pains and other clinical manifestations of secondary synovitis but also has positive effect on the structure of articular cartilage.